Application of the Correlation Matrix in Variable Cell Mechanism Design - Lin Jin (Jixie chuandong)
With the deepening of the variable cell organization research,the flexibility of its continuous structure state change,the mechanism using versatility is gradually highlight. Combining with more poles structure construction method,the variable cell organization in promoting the feasibility of turning operation of the specific occasion is analyzed. In view of the common cell types,the topology structure change is analyzed,the mathematical tool of matrix is put forward to describe state modulator cell organization change process. The matrix contains motion pair type,reflect kinematic pair and the number of components,and the structure is simple,the description is complete,it is convenient for computer programming and logic operation,widely applicable to all kinds of cell organization analysis research work.